Synthesis and Characterization of Some New Metallo-Organic Derivatives of Germanium(IV) - Samuel, Blassan; Tummalapalli, Kiran; Vuppalapati Giri, Prasanth; An, Arun; Pathak, Madhvesh (Asian Journal of Chemistry, 2014)
Compounds of the type GeGn(OR)4-2n [where G = O(CH2)2S(CH2)O, S(CH2)2O(CH2)2S, S(CH2)2S(CH2)2S; R = Et, Pri and n = 1, 2] have been prepared by the reaction of Ge(OR)4 with 2-hydroxyethyl sulfide, 2-mercaptoethyl ether and 2-mercaptoethyl sulfide in 1:1 and 1:2 molar ratios in refluxing anhydrous benzene. All these complexes are white sticky solid in appearance. After purification and spectral analyses (IR and 1H and 13C NMR) tetra coordination geometry is proposed around germanium atom.